2017
DOI: 10.1063/1.4974752
|View full text |Cite
|
Sign up to set email alerts
|

Role of aluminum in silver paste contact to boron-doped silicon emitters

Abstract: The addition of aluminum to silver metallization pastes has been found to lower the contact resistivity of a silver metallization on boron-doped silicon emitters for n-type Si solar cells. However, the addition of Al also induces more surface recombination and increases the Ag pattern′s line resistivity, both of which ultimately limit the cell efficiency. There is a need to develop a fundamental understanding of the role that Al plays in reducing the contact resistivity and to explore alternative additives. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For the formation of ohmic contact on the boron-doped emitter, since the mechanism is more complicated, many attempts have been made to improve the semiconductor-metal contact. Some reports have proved that the contact resistivity between the electrode and the Si substrate could be remarkably reduced by adding aluminum particle to the Ag paste to form silver-aluminum (Ag-Al) paste [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. On the other hand, with the presence of the Al particle, some inappropriate Ag/Al spikes can give birth to a larger dark saturation current beneath the paste contact area [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the formation of ohmic contact on the boron-doped emitter, since the mechanism is more complicated, many attempts have been made to improve the semiconductor-metal contact. Some reports have proved that the contact resistivity between the electrode and the Si substrate could be remarkably reduced by adding aluminum particle to the Ag paste to form silver-aluminum (Ag-Al) paste [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. On the other hand, with the presence of the Al particle, some inappropriate Ag/Al spikes can give birth to a larger dark saturation current beneath the paste contact area [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Al is added to the Ag conductive paste to increase the contact points. The contact resistivity may be reduced about three orders of magnitude, because the silver/aluminum paste creates large and deep metal spikes [26,27]. If a high amount of Al is added to the Ag paste, the leakage currents of the solar cell increases due to large Al spikes [28].…”
Section: Introductionmentioning
confidence: 99%
“…The particle size of the aluminum powder affects the contact resistivity, which decreases with the increasing of Al particle size [26]. Wu et al [27] reported a microstructural study of the contact of the Ag/Al conductive paste with boron doped emitters, that indicated the formation of microscale metallic spikes of Al-Ag alloy and nanoscale metallic spikes of Ag-Si alloy, that allow the direct contact to the emitter.…”
Section: Introductionmentioning
confidence: 99%
“…For a front side emitter, the typical industrial metallization approach is based on screen‐printing and firing of a silver‐aluminum (Ag‐Al) paste. It has been shown that it is necessary to add a small percentage of Al to the Ag paste in order to achieve low specific contact resistances ρ C in the range of a few mΩ cm 2 . However, these Ag‐Al contacts especially trigger increased charge carrier recombination below the metallized areas leading to severe open‐circuit voltage losses and hence, energy conversion efficiency losses.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the lack of crystallites at the interface (e.g., Refs. report on ρ C in the range of several tens of mΩ cm 2 for Ag contacts on boron‐doped surfaces).…”
Section: Introductionmentioning
confidence: 99%